UTILIZATION OF INDONESIAN LOCAL STANNIC CHLORIDE (SnCl4) PRECURSOR IN THE PROCESS OF MAKING FLUORINE- DOPED TIN OXIDE (FTO) CONDUCTIVE GLASS - Tri Arini; Latifa Hanum Lalasari; Lia Andriyah; Gennady Fahmi; F. Firdiyono (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2019)
UTILIZATION OF INDONESIAN LOCAL STANNIC CHLORIDE (SnCl4) PRECURSOR IN THE PROCESS OF MAKING FLUORINE-DOPED TIN OXIDE (FTO) CONDUCTIVE GLASS. Thin layer of fluorine- doped tin oxide (FTO) conductive glass has been deposited on a glass substrate heated at a temperature of 350°C using the ultrasonic spray pyrolysis nebulizer method with variations in fluorine doping and substrate temperatures. This experiment uses the raw material of Indonesian local stannic chloride (SnCl4) (PT Timah Industri) as a precursor with a temperature variation of 250, 300, 350, 400°C. The structure and morphology of the optical and electrical properties of all the thin layers have been examined. XRD results show that all thin layers have a tetragonal crystal structure. In this experiment, there is a significant influence on the role of fluorine doping on resistivity and transmittance values. With the addition of 2% wt doping, the resistivity and transmittance values decrease. The optimum value is obtained by doping 2 wt%, substrate temperature of 350°C with a resistivity value of 9.28.10-5 Ω.cm and transmittance value of 88%.